Being a YouTuber that language learners recognize: A study on constructing language teacher identities in social media community of practice. (October 2022) - Chao, Chin-chi
Abstract: Despite increased studies on language teacher identities (LTIs) in digital contexts, there has not been much research on constructing LTIs in social media (SM), a unique community of practice featuring interaction between the language teacher community oriented toward classroom practice and the SM community featuring participatory culture and visibility – allowing one to be seen. This study filled the gap by focusing on two language teaching YouTubers' construction of LTIs by analyzing multiple runs of narratives, in-depth interviews, and their video work. Wenger's (1998) social ecology of identity in community of practice (CoP) was adopted as the analytic framework. The findings reveal that one participant was positioned as a classroom teacher to the audience right from the very beginning, aligned her work with the language teacher community, and felt marginalized, while the other positioned herself as a knowledgeable peer, not a teacher, aligned more with the SM community, and felt more empowered. Their experiences of participation and marginalization reveal the importance of keeping a balance between the self and audiences and challenge the conventional view that language teaching in SM is all about fun and entertaining. Implications and suggestions for SM language teaching and research are provided.